The imaginary of the city versus messy realities. (16th January 2020) - Stafford, Anne; Stapleton, Pamela; Wei, Hua; Williams, Karel
Abstract: Accounting research on transport has been narrowly focused on cost recovery and the consequences of privatization and restructuring. Accounting researchers have not engaged with the now dominant orthodoxy about cities as agglomeration argued by urbanists like Glaeser or championed earlier critical understandings of the limits of urban planning argued by Jane Jacobs. Working within that critical tradition, this paper innovates by presenting an exploratory and interdisciplinary case study of public transport in the city of Greater Manchester, which draws on accounting and other evidence. Policy makers have represented the construction of Manchester's new tram system as a major success but we argue that the system represents an ill‐judged investment priority, which had unintended consequences for the whole public transport system. Part of the problem is classic top down failure to engage local specifics because the tram network has added a radial system to a city with untidy orbital movement patterns and diverse mobility requirements. This awkward gap between the imaginary of the policy makers and messy realities has financial consequences because the capital costs of tram increasingly squeeze the ability of the public transport authority to subsidize the bus services, which carry 10 times as many passengers as tram. The political question is whether and how this kind of argument and evidence can inform popular politics and shift what is taken for granted by experts and the political classes in Manchester.